Structure Determination of a Chloroenyne from Laurencia majuscula Using Computational Methods and Total Synthesis - Shepherd, Erin D. (J Org Chem, 2019)
[Image: see text] Despite numerous advances in spectroscopic methods through the latter part of the 20th century, the unequivocal structure determination of natural products can remain challenging, and inevitably, incorrect structures appear in the literature. Computational methods that allow the accurate prediction of NMR chemical shifts have emerged as a powerful addition to the toolbox of methods available for the structure determination of small organic molecules. Herein, we report the structure determination of a small, stereochemically rich natural product from Laurencia majuscula using the powerful combination of computational methods and total synthesis, along with the structure confirmation of notoryne, using the same approach. Additionally, we synthesized three further diastereomers of the L. majuscula enyne and have demonstrated that computations are able to distinguish each of the four synthetic diastereomers from the 32 possible diastereomers of the natural product. Key to the success of this work is to analyze the computational data to provide the greatest distinction between each diastereomer, by identifying chemical shifts that are most sensitive to changes in relative stereochemistry. The success of the computational methods in the structure determination of stereochemically rich, flexible organic molecules will allow all involved in structure determination to use these methods with confidence.